Stroke in Acquired and Congenital Heart Disease Patients and Its Relationship to Hospital Mortality and Lasting Neurologic Deficits. Issue 10 (October 2016) - Cheng, Henry H.; Rajagopal, Satish; McDavitt, Erica; Wigmore, Daniel; Williams, Kathryn; Thiagarajan, Ravi; Grant, P. Ellen; Danehy, Amy; Rivkin, Michael J.
Abstract : Objective: To describe strokes in patients with acquired or congenital heart disease and investigate risk factors for in-hospital mortality and ongoing neurologic deficits. Design: Single-center, retrospective review of cardiac, neurologic, and radiologic patient databases. Setting: Tertiary care children's hospital. Patients: All patients with acquired or congenital heart disease admitted from January 2010 to October 2014 identified with stroke. Interventions: None. Measurements and Main Results: Eighty-four stroke events were identified in 83 patients (median age, 5.9 mo; interquartile range, 0.8–33.4). Thirty-two patients (38%) had single ventricle congenital heart disease. Eight patients (9%) presented with symptoms at home, and the remainder was diagnosed while already admitted to the hospital. Forty patients (48%) presented with clinically evident neurologic deficits (e.g., weakness, seizures). Fifty-eight patients (69%) had arterial ischemic strokes, and 13 (15%) had parenchymal hemorrhages. At diagnosis, 54 patients (64%) were on inotropes. Twenty-nine patients (35%) had greater than or equal to 3 cardiac procedures during their hospitalization before stroke diagnosis. In-hospital mortality occurred in 28 patients (33%). Under multivariate analysis, inotropes, number of cardiac procedures, lack of seizure, and parenchymal hemorrhage were independently associated with in-hospital mortality ( p < 0.05). Fifty-four percent of survivors with neurologic follow-up had ongoing neurologic deficits attributable to strokes (median follow-up, 15.3 mo; interquartile range, 7.0–29.9). With multivariate analysis, longer hospital stay ( p = 0.02) was independently associated with ongoing deficits. Conclusions: A majority of patients with acquired or congenital heart disease who suffer stroke present while hospitalized and without focal neurologic findings. In-hospital mortality is associated with inotropes, cardiac procedures, lack of seizure, and parenchymal hemorrhage. The majority of survivors have lasting neurologic deficits associated with longer hospital stay. Abstract : Supplemental Digital Content is available in the text.